2022
DOI: 10.3389/fnut.2022.911315
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol monolaurate ameliorates DSS-induced acute colitis by inhibiting infiltration of Th17, neutrophils, macrophages and altering the gut microbiota

Abstract: Background and aimsInflammatory bowel disease (IBD) places a heavy medical burden on countries and families due to repeated and prolonged attacks, and the incidence and prevalence of IBD are increasing worldwide. Therefore, finding an effective treatment is a matter of great urgency. Glycerol monolaurate (GML), which has a twelve-carbon chain, is a compound naturally found in human breast milk. Some studies have shown that GML has antibacterial and anti-inflammatory effects. However, the specific mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Moreover, GML showed immunomodulatory activities as evidenced by inhibited T cell receptor ( TCR )-induced the production of the cytokines IL-2, IFN-γ, TNF-α, and IL-10 ( Zhang, 2018 ). Glycerol monolaurate alleviates dextran sodium sulphate ( DSS )-induced colitis by increasing the expression of anti-inflammatory cytokines (IL-10, TGF-β), and decreasing the expression of proinflammatory cytokines (TNF-α, IL-1β, IL-1α) ( He et al, 2022 ). Mo et al (2019) demonstrated that GML modulated the composition of gut microbiota and short chain fatty acid concentrations in a dose-dependent manner to improve intestinal health in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GML showed immunomodulatory activities as evidenced by inhibited T cell receptor ( TCR )-induced the production of the cytokines IL-2, IFN-γ, TNF-α, and IL-10 ( Zhang, 2018 ). Glycerol monolaurate alleviates dextran sodium sulphate ( DSS )-induced colitis by increasing the expression of anti-inflammatory cytokines (IL-10, TGF-β), and decreasing the expression of proinflammatory cytokines (TNF-α, IL-1β, IL-1α) ( He et al, 2022 ). Mo et al (2019) demonstrated that GML modulated the composition of gut microbiota and short chain fatty acid concentrations in a dose-dependent manner to improve intestinal health in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol monolaurate has also been shown to inhibit B cell receptor-induced cytokine production, phosphorylation of signaling proteins, and protein clustering ( Fosdick et al, 2022 ). Moreover, oral administration of GML inhibits the infiltration of macrophages and reduces the expression of proinflammatory factors, thereby contributing to the alleviation of experimental colitis in mice ( He et al, 2022 ). However, the modulatory effects of GML on avian macrophages are not yet known.…”
Section: Introductionmentioning
confidence: 99%
“… Th17 cells secrete cytokines interleukin-17 (IL-17), which stimulates the secretion and expression of several inflammatory factors and chemokines, such as IL-6, TNF-α, IL-1β, and IL-22, by activating the NF-κB and MAPK pathways. This leads to the recruitment and activation of multiple immune cells, causing or worsening tissue inflammation. Targeting Th17 cells has become a promising approach to treat inflammatory diseases. The production of Th17 cells from CD4 + T cells is tightly regulated by chromatin gene transcription, a complex process involving the collective activity of critical transcription factors. Among them, the bromodomain and extra terminal domain (BET) proteins play significant roles in the complex process. The classical Pan-BET inhibitor JQ-1 has been shown to effectively suppress the Th17 cell differentiation …”
Section: Introductionmentioning
confidence: 99%